Characteristics of Ag Element on LSCF-SDCC-Ag Composite Cathode for LTSOFC Potential Applications - Abu Bakar, Mohd Subri; Ahmad, Sufizar; Mohammad, Siti Fairus; Rahman, Hamimah Abdul (Journal of Advanced Mechanical Engineering Applications, 2019)
In this research, composite cathode of Lanthanum Strontium Cobalt Ferrite-Samarium Doped Ceria Carbonate-Argentum (LSCF-SDCC-Ag) for low temperature SOFC (LTSOFC) as potential applications were investigated clearly.  Research has been focused on the influence of Ag as an additive element, on improvement and properties of LSCF-SDCC-Ag composite cathode powder. Composite cathode powders LSCF-SDCC-Ag with Ag addition of 1-5 wt.% has been prepared using high energy ball milling (HEBM) technique and sintered at temperatures of 500-600 ËšC. The prepared samples were characterized using X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) and Energy Dispersive Spectroscopy (EDS). From XRD analysis of LSCF-SDCC-Ag composite cathode powder exhibited good chemical compatibility, as there were no secondary constituent was detected via XRD sensitivity. It can be observed carbonate phase in LSCF-SDCC-Ag managed to maintain their phase as confirmed via FTIR analysis. Meanwhile, the quantitative elements for the LSCF-SDCC-Ag composite cathode powder which has been identified using EDS revealed that from HEBM technique, permitted the cathode to achieve a nano-composite state powder characteristic. Hence, from XRD, FTIR and EDS analysis concluded that the LSCF, SDCC and Ag were compatible with each other in forming the composite cathode LSCF-SDCC-Ag for LTSOFC applications.